‘You Choose No Time to Live and Die’: Dinmukhamed A. Kunayev and His Time - Ziyabek Y. Kabuldinov; Konstantin V. Cherepanov; Didar B. Kassymova (Oriental Studies)
Introduction. The article deals with the life and endeavors of Dinmukhamed А. Kunayev ― a prominent Soviet statesman and party activist, who was long in charge of the Kazakh SSR Party Organization and greatly contributed to socioeconomic development of the Republic (and the whole Soviet Union) in 1942–1986. Goals. The article shall examine documentary sources pertaining to D. Kynayev’s life path to highlight his role in the Republic’s economic, scientific, and political development, emphasize his contribution to the preservation and successes of the Soviet state at large, and appreciate his significance to the birth of sovereign Kazakhstan (and its territorial integrity). Materials and methods. The study covers a variety of sources, including personal memories of D. Kunayev, recollections of his contemporaries and co-workers, materials and documents from Kazakhstan-based and foreign archives (Archive of the President of the Republic of Kazakhstan, Central State Archive of the Republic of Kazakhstan, etc.). The article employs the historical-genetic and historical-comparative methods, addresses the concept of biographic approach and theory of ethnic mobilization to reconstruct some episodes of D. Kunayev’s biography in certain historical contexts with due regard of related national/ethnic mobilizing components. Much in Kunayev–Moscow relations can be explained by provisions of clientilism theory. Such methods of sociological research as discourse analysis of texts and speech patterns of Soviet Union and Kazakhstan’s executives have proven as instrumental. Conclusions. The paper shows D. Kunayev played a remarkable role in the development of all spheres of Soviet Kazakhstan, and either did he for the development of the whole Soviets, which also provided certain grounds for subsequent successful development of independent Kazakhstan.